UML-Based Web Information System for Indonesian Migrant Worker Recruitment: A Case Study at PT Dewi Pengayom Bangsa - Ramanda, Febri; Afriyani, Risti; Sella, Puspita Sari; Ardika, Kevin (Jurnal Media Elektrik, 2026)
Objective: Private Indonesian migrant worker placement agencies, such as PT Dewi Pengayom Bangsa in Pati Regency, still rely on paper-based and inefficient manual recruitment processes. These processes face issues such as slow data retrieval, excessive physical storage demands, and document accumulation. This study aimed to develop a web-based information system to digitize the recruitment workflow of Indonesian migrant workers (Calon TKI) in Taiwan, Hong Kong, and Singapore. Method: A systems development approach using the waterfall model was employed. Data were collected through on-site observation and semi-structured interviews with agency staff and management, complemented by secondary data from the literature on information systems and migrant labor policies. The system was designed using UML diagrams and implemented using PHP and MySQL. The evaluation included black-box testing and usability assessments. Results: The system integrated eight core modules: online registration, candidate management, automated examination, interview recording, and real-time PDF reporting. Testing showed a 100% success rate in black-box testing and an average usability score of 82.3. Efficiency improvements were substantial: registration time was reduced by 82%, data retrieval improved by 95%, and data entry errors dropped by 92%. Novelty: This study introduces a UML-modeled web-based recruitment system tailored for private TKI agencies at the regency level, offering significant efficiency gains and supporting Indonesia’s BP2MI policies.